2004
DOI: 10.1108/09600030410526914
|View full text |Cite
|
Sign up to set email alerts
|

People and information technology in the supply chain

Abstract: Understanding people and how they factor into complex information technology (IT) implementations is critical to reversing the growing trend of costly IT implementation failures. Accordingly, this article presents an approach to dissecting the social and organizational influences impacting peoples’ acceptance of technology designed to improve business performance. This article applies the diffusion of innovation theoretical framework to understand and analyze IT innovation implementation challenges. The diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(48 citation statements)
references
References 17 publications
0
48
0
Order By: Relevance
“…Interviews with experts have been extensively used in the literature with regard to this industry, and numerous case studies have been done (Russell and Hoag 2004, Zsidisin and Smith 2005, Laframboise and Reyes 2007, Esposito and Passaro 2009. The focus group is one of the most widely used research tools in social sciences, and previous studies were found in the literature that use these in the area that concerns this study, operations management in general (Dey et al 2006, Binder andEdwards 2010) and SCM in particular (Oehmen et al 2010, Tate et al 2010.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Interviews with experts have been extensively used in the literature with regard to this industry, and numerous case studies have been done (Russell and Hoag 2004, Zsidisin and Smith 2005, Laframboise and Reyes 2007, Esposito and Passaro 2009. The focus group is one of the most widely used research tools in social sciences, and previous studies were found in the literature that use these in the area that concerns this study, operations management in general (Dey et al 2006, Binder andEdwards 2010) and SCM in particular (Oehmen et al 2010, Tate et al 2010.…”
Section: Methodsmentioning
confidence: 97%
“…et al (2004);Reed and Walsh (2002);Rota et al (2002);Russell and Hoag (2004); Zuckerman (2007) CRS Anderson (1995); Bales et al (2004); Bozdogan et al (1998); Esposito and Passaro (2009); Gary and Pervaiz (2000); Grant (2003); Paliwoda and Bonaccorsi (1994); Farris et al (2005); Sinha et al (2004); Smith and Tranfield (2005) ORL Anderson (1995); Bales et al (2004); Brookes et al (2007); Cagliano et al (2005); Esposito and Passaro (2009); Farris et al (2005); Frear and Metcalf (1995); Gary and Pervaiz (2000); Morton et al (2006); Paliwoda and Bonaccorsi (1994); Sinha et al (2004); Rose-Anderssen et al (2008); Smith and Tranfield(2005)…”
mentioning
confidence: 98%
“…A meta analysis of the technological innovation studies found that the first three attributes have the most significant impacts on the IT innovation diffusion (Tornatzky and Klein 1982). Later studies mostly focused on three attributes of IT innovation, that is, relative advantage, compatibility and complexity (Thong 1999;Russell and Hoag 2004;Yu and Tao 2009). Although particular factors identified within technology context may vary across different studies, considering ERP context we consider these three attributes, which are commonly recognized as the most important technological drivers in ERP assimilation.…”
Section: Technology Aspectmentioning
confidence: 97%
“…Studies conducted in 2007 in the US and Europe found that the existing BIM software is too complex to be used by most project team members (Gilligan & Kunz, 2007;Howard & Björk, 2008). Existing literature on innovation diffusion has shown that the rate of adoption decreases with the increase in implementation complexity of an innovation (Howard & Björk, 2008;Kunz, J. and Fischer, 2007;Newton & Chileshe, 2012;Russell & Hoag, 2004). That is, there is increased possibility of adoption if innovation is less complicated and is easy to use.…”
Section: Complexitymentioning
confidence: 99%